Art byzantin et peintres français au XIXe siècle sur le Mont Athos - Katerina Seraïdari (Images du Travail, Travail des Images)
The article examines the interest, which arose around Byzantine art in France around the 1840s and which led to the discovery of Panselinos’ work on Mount Athos, but also of a tradition favoring a collective way of doing – this artistic tradition being already threatened by Russian influence. Two French painters are at the center of the article: Alexandre Bida, who painted the Refectory of Greek monks on Mount Athos but who, apparently, never visited this place; and Dominique Papety, who stayed there for a little more than a week during the summer of 1846 but who made a great number of drawings during his visit. The work of these painters shows Mount Athos as a place of artistic production, conservation and transmission. It also places this monastic peninsula and its inhabitants, deliberately staying at the margins of society, in the center of artistic debates in France.